호흡 순환기 질환자의 지각된 스트레스, 미세먼지 위험 인식, 극복력이 스트레스 반응에 미치는 영향 - 박진희(Jin-Hee Park); 한금선(Kuem-Sun Han) (Seuteureseu yeon-gu (Online), 2021)
본 연구는 호흡 순환기 질환자의 지각된 스트레스, 미세먼지 위험 인식, 극복력의 정도를 확인하고 이들 변수 간의 관계를 규명함으로써 지각된 스트레스, 미세먼지 위험인식, 극복력이 스트레스 반응에 미치는 영향을 확인하고자 시도된 서술적 상관관계 연구이다. 만 20세 이상의 호흡기 및 순환기 질환자 184명을 대상으로 설문조사를 실시하였으며, SPSS 프로그램을 이용하여 분석하였다. 호흡 순환기 질환자의 스트레스 반응에 영향을 미치는 요인은 지각된 스트레스, 극복력, 가족관계, 질환의 종류로 나타났다. 본 연구를 통한 호흡 순환기 질환자의 지각된 스트레스, 극복력, 가족관계, 질환의 종류 파악은 스트레스 반응을 예방하는데 유용한 기초자료로 활용되어 호흡 순환기 질환자의 스트레스 간호에 기여하리라 사료된다. Background: The purpose of this study is to determine the degree of perceived stress, fine dust risk perception, and resilience in patients with respiratory and circulatory disorders, and investigate the relationship between these variables. Methods: A questionnaire survey was conducted on 184 patients with respiratory and circulatory diseases over the age of 20 and analyzed using descriptive statistics, Pearson’s correlation coefficient, and stepwise regression analysis using the SPSS program. Results: The study found perceived stress, resilience, family relationship, and type of disease to be factors affecting the stress response of people with respiratory and circulatory disorders. Conclusions: Understanding the perceived stress, resilience, family relationship, and type of respiratory and circulatory disorder prevents stress response and contributes to stress nursing. KCI Citation Count: 1